Endolichenic fungus, Aspergillus quandricinctus of Usnea longissima inhibits quorum sensing and biofilm formation of Pseudomonas aeruginosa PAO1. (March 2020) - Prateeksha; Bajpai, Rajesh; Yusuf, Mohd Aslam; Upreti, Dalip Kumar; Gupta, Vijai Kumar; Singh, Brahma Nand
Abstract: Lichens are composite organisms, comprising of a fungus (mycobiont) and a blue-green alga (photobiont). Along with the mycobiont, numerous non-obligate microfungi live in lichen thalli. These microfungi are called endolichenic fungi (ELF). In recent years, the ELF are emerging as promising natural sources because of their capability to exert unique drug molecules. The current study aimed to isolate the ELF from the lichen, Usnea longissima Ach., to control of biofilm formation and quorum sensing phenomenon in Pseudomonas aeruginosa PAO1, an opportunistic multidrug resistance pathogen that uses quorum sensing network to produce an array of pathogenic agents. Therefore, inhibiting quorum sensing to manage the infection caused by PAO1 could be the paramount alternative approach to conventional antibiotics. The isolated ELF was identified by amplifying the long subunit region of the fungal genome. The extracted metabolites of ELF (MELE) using the acetone solvent was further investigated for anti-quorum sensing activity using the biomarker strain Chromobacterium violaceum 12472 which exerts violacein pigment via the AHL mediated quorum sensing signalling. Moreover, the effect of MELE was also evaluated on the production of virulence factors and biofilm formation of P. aeruginosa PAO1. The molecular identification revealed that ELF (accession number MN171299) exhibited 100% similarity with Aspergillus quandricinctus strain CBS 135.52. The MELE showed significant anti-quorum sensing activity at the concentration of 4 mg/mL without affecting the bacterial cell viability of P. aeruginosa PAO1. The MELE diminished the production of virulence factors, including pyocyanin, protease, elastase, rhamnolipids, and extracellular polysaccharides of P. aeruginosa PAO1 in a concentration-dependent manner. The MELE also disturbed biofilm formation of P. aeruginosa PAO1. The 3-D analysis of biofilm architecture showed that the thickness and surface area covered by microcolonies was decreased as the concentration of MELE was increased. The GC-MS analysis of MELE exhibited that organic acids and fatty acids are major constituents of the MELE. The present study reports first time that the ELF, A. quandricinctus possesses potential to inhibit quorum sensing and biofilm formation of P. aeruginosa and can be further exploited for hospital and healthcare facilities. Highlights: Aspergillus quandricinctus, an endolichenic fungi (ELF) from Usnea longissimia. The acetone extract of A. quandricinctus (MELF) inhibits the quorum sensing-regulated production violacein pigment. The MELF quenches the pathogenic determinants of Pseudomonas aeruginosa. The MELF inhibits the biofilm formation of P. aeruginosa. The present study raises the possibility to utilize the ELF as hospital health-care facilities.